mm-Wellen- und Electronic-Photonic System-on-Chip Design - Scheytt, Christoph (Fakultätskolloquium der Fakultät für Elektrotechnik und Informationstechnik)

Electro-optic tuning of split ring resonators embedded in a liquid crystal - Atorf, Bernhard; Mühlenbernd, Holger; Muldarisnur, Mulda; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Optics Letters)

Effect of Alignment on a Liquid Crystal/Split-Ring Resonator Metasurface - Atorf, Bernhard; Mühlenbernd, Holger; Muldarisnur, Mulda; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (ChemPhysChem)

Polycyclic Aromatic Hydrocarbons Obtained by Lateral Core Extension of Mesogenic Perylenes: Absorption and Optoelectronic Properties - Vollbrecht, Joachim; Bock, Harald; Wiebeler, Christian; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (Chemistry - A European Journal)

Entwicklung diagnostischer Fähigkeiten bei Lehramtsstudierenden - Hellmich, Frank; Hoya, Fabian Karl (Individuelle Förderung und Lernen in der Gemeinschaft)

Kann Betroffenheit Gleichheit ersetzen? Eine Analyse der Prinzipien des normativen Individualismus - Hagengruber, Ruth Edith (Normativer Individualismus in Ethik, Politik und Recht)

Philosophy, Computing and Information Science

Sychowski, Gaja von: Geschlecht und Bildung. Beiträge der Gender-Theorie zur Grundlegung einer Allgemeinen Pädagogik im Anschluss an Judith Butler und Richard Hönigswald (Würzburg: Königshausen & Neumann, 2011) - Hagengruber, Ruth Edith (Journal des Netzwerks – Frauen und Geschlechterforschung NRW)

Dietmar von der Pfordten: Normative Ethik (Berlin/New York: Walter de Gruyter, 2010) - Hagengruber, Ruth Edith (Philosophisches Jahrbuch)

An inclusive school system in Rhineland-Palatinate? Results of a research project and their relevance for international research on inclusive education. - Laubenstein, Désirée; Scheer, D.

Wie gelingt Inklusion? Symposium im Rahmen der GEBF-Tagung - Laubenstein, Désirée

Projektvorstellung GeSchwind. Ministerium für Bildung, Weiterbildung, Wissenschaft und Forschung. Mainz. 15.01.2014. - Laubenstein, Désirée

Alltagskultur: viel beschworen, wenig wissenschaftlich durchdrungen?! - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Hauswirtschaft und Wissenschaft)

Playing hard to get: an economic rationale for crowding out of intrinsically motivated behavior - Schnedler, Wendelin; Vanberg, Christoph (European Economic Review)

Die Wikinger und das Fränkische Reich. Identitäten zwischen Konfrontation und Anpassung

Libéralité et dilapidation dans l'Empire du Haut Moyen Âge - Kamp, Hermann (La dilapidation de l'Antiquité au XIXe siècle)

Päpste als Friedensvermittler in der Karolingerzeit - Kamp, Hermann (Christliche Friedensethik im frühen Mittelalter)

Die Wikinger und das Fränkische Reich. Identitäten zwischen Konfrontation und Anpassung

99 Tipps für Englisch - Hohwiller, Peter

IFRS 7 Disclosures and Risk Perception of Financial Instruments - Bischof, Jannis; Ebert, Michael (Schmalenbach Business Review)

Validierung eines Instruments zur Erfassung der professionellen Handlungskompetenz von (angehenden) Physiklehrkräften. Zusammenhangsanalysen zwischen Lehrerkompetenz und Lehrerperformanz - Vogelsang, Christoph

Donna Haraway. Technoscience, New World Order und Trickster-Geschichten für lebbare Welten - Weber, Jutta (Schlüsselwerke der Wissenschafts- und Technikforschung / Science & Technology Studies)

Hands-Free Driving? Automatisiertes Fahren und Mensch-Maschine Interaktion - Weber, Jutta; Both, Göde (Robotik im Kontext von Moral und Recht)

Technoscience als Populärkultur. Über magische Medien, neue Konsumtechnologien und neoliberale Aufmerksamkeitsökonomien - Weber, Jutta (Strukturwandel der Wissenschaft. Positionen zum Epochenbruch)

Wild Cards. Imagination als Katastrophenprävention - Weber, Jutta (Zeitschrift für Kulturwissenschaft, Sonderausgabe zum Thema ‚Vorstellungskraft‘ (Hg.: Siegfried Mattl, Christian Schulte))

Opacity versus Computational Reflection. Modelling Human-Robot Interaction in Personal Service Robotics - Weber, Jutta (Science, Technology and Innovation Studies. Vol. 10, No.1, January 2014)

Autonom tötende Maschinen - Weber, Jutta (Autonome Automaten. Künstliche Körper und artifizielle Agenten in der technisierten Gesellschaft)

Architectural Low-Power Design Using Transaction-Based System Simulation - Mischkalla, Fabian; Müller, Wolfgang (Embedded Computer Systems: Architectures, Modeling, and Simulation (SAMOS XIV))

Source code annotated memory leak detection for soft real time embedded systems with resource constraints - Joy, M. tech. Mabel Mary; Müller, Wolfgang; Rammig, Franz-Josef (12th IEEE International conference on Embedded Computing)

Advanced SoC Virtual Prototyping for System-Level Power Planning and Validation - Mischkalla, Fabian; Müller, Wolfgang (PATMOS 2014)

Fault Effect Modeling in a Heterogeneous SystemC Based Virtual Platform Framework for Cyber Physical Systems - Becker, Markus; Kuznik, Christoph; Müller, Wolfgang
This paper presents an advanced eight levels spanning SystemC based virtual platform methodology and framework - referred to as HeroeS 3 - providing smooth application to platform mapping and continuous co-refinement of a virtual prototype with its physical environment model. For heterogeneity support, various SystemC extensions are combined covering continuous/discrete models of computation and different communication abstractions, such as analog mixed-signal models, abstract RTOS/HAL/middleware models, TLM bus models, and QEMU wrappers. We enable dependability assessment by Fault Effect Modeling (FEM) at the virtual prototype in order to avoid risking physical injury or damage. Also, simulation results are deterministic and can be evaluated interactively or offline. We apply FEM to both the physical environment model and the different abstractions of the virtual prototype. Currently, we focus on sensor failures and application control flow errors.
Keywords: Computational modeling; Finite element analysis; Prototypes; Abstracts; Software; Fault tolerance; Fault tolerant systems

An Assisted Single Source Verification Metric Model Code Generation Methodology - Kuznik, Christoph; Müller, Wolfgang; Defo, Gilles Bertrand
The ever-increasing complexity of heterogeneous electronic systems demand for intensified abstraction and automation efforts to improve design, verification and validation productivity, especially in earlier phases of system engineering. Within the verification activity various metrics can be applied to determine functional correctness or the overall progress. Here, a supporting verification methodology defining high-level verification planning down to the actual metric code development is essential. Moreover, an advanced assistance for the designer, such as a tooling infrastructure to automatize and accelerate the metric code implementation, is needed to minimize the influence of errorprone manual coding. In this article we present a single-source verification metric code-generation methodology for improved coverage automation. We determine (i) a suitable metric model for model-based capture of verification metrics as well as (ii) an assisted model-based processing and generation flow of the verification environment and metric skeletons. We apply our method to a SystemC case-study, in doing so, targeting metric code implementation productivity and consistency enhancement.
Keywords: System Design; Verification

Modellierung effizienter Stresstest-Umgebungen für virtuelle Prototypen mit SVM - Kuznik, Christoph; Müller, Wolfgang (26. ITG / GI / GMM Workshop Testmethoden und Zuverlässigkeit von Schaltungen und Systemen)
Zur Sicherstellung hoher Zuverlässigkeits- und Fehlertoleranzwerte von Schaltungen und ganzen Systemen finden vermehrt Test- und Verifikationsmethoden Anwendung die einen virtuellen Prototypen (VP) des Systems bereits frühzeitig im Entwurfsablauf einem Stresstest unterziehen. Hierbei werden speziell für die Domäne relevante Fehlerinjektoren verwendet (Digital, Mixed-Signal, Mechanik) die anhand von Fehlermodellen geeignete Testfälle erzeugen und in das System über Stimuli bzw. direkt injizieren. Jede effektive Anwendung einer Methode bedingt jedoch auch das Vorhandensein einer zugrundeliegenden Methodik. In diesem Beitrag wird die System Verification Methodology (SVM) vorgestellt werden, eine universell einsetzbare und erweiterbare Infrastruktur zur Beschreibung von Testumgebungen auf Basis der SystemC Sprache und Simulationskernels.

Semi-automatische Generierung von Überdeckungsmetriken mittels methodischer Verikationsplan Verarbeitung - Kuznik, Christoph; Defo, Bertrand Gilles; Müller, Wolfgang (17. Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV 2014))

An Assisted Single Source Verification Metric Model Code Generation Methodology - Kuznik, Christoph; Defo, Bertrand Gilles; Müller, Wolfgang (Electronic System Level Synthesis Conference (ESLSyn))

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska

Rechtssprachliches im >Vocabularius Theutonicus< - Wallmeier, Nadine (Studien zur Lexikographie und Lexikologie des Niederdeutschen. Festgabe für Robert Damme zum 60. Geburtstag.)

Lecture meets laboratory experimental experiences for large audiences: Concept and implementation - Temmen, Katrin; Nofen, Barbara; Wehebrink, Markus (2014 IEEE Global Engineering Education Conference (EDUCON))

The Capability Approach and Sociological Conceptions of Human Agency: An Empirical Assessment on the Basis of an Analysis of Activation Policies - Dahmen, Stephan (Social Work & Society. International Online Journal)

The Theoretical Orthodoxy of Children’s and Youth Agency and Its Contradictions: Moving from Normative Thresholds to a Situated Assessment of Children’s and Youth Lives - Dahmen, Stephan (Children’s Rights and the Capability Approach)

Cost of Debt for Private Firms Revisited: Voluntary Audits as a Reflection of Risk - Koren, Jernej; Kosi, Urska; Valentincic, Aljosa

Improving reading in children with German as a first or second language - Schwab, Susanne; Seifert, Susanne; Gasteiger-Klicpera, Barbara (International Journal of Early Years Education)
Keywords: Developmental and Educational Psychology; Education

Einstellungen von Lehramtsstudierenden und Pädagogikstudierenden zur schulischen Inklusion – Ergebnisse einer quantitativen Untersuchung - Schwab, Susanne; Seifert, Susanne (Zeitschrift für Bildungsforschung)

Donna Haraway. Technoscience, New World Order und Trickster-Geschichten für lebbare Welten - Weber, Jutta (Schlüsselwerke der Wissenschafts- und Technikforschung/Science & Technology Studies)

Opacity versus Computational Reflection. Modelling Human-Robot Interaction in Personal Service Robotics - Weber, Jutta (Science, Technology and Innovation Studies, Vol. 10, No. 1)

Resonance chains in open systems, generalized zeta functions and clustering of the length spectrum - Barkhofen, Sonja; Faure, F; Weich, Tobias (Nonlinearity)
Keywords: Applied Mathematics; General Physics and Astronomy; Mathematical Physics; Statistical and Nonlinear Physics

Zugezogene im Fokus. Sprachkontakterscheinungen im Regiolekt. - Lorenz, Cornelia

Salienz unter Einheimischen und Zugezogenen. Ein empirischer Vergleich. - Lorenz, Cornelia (Linguistik Online)

Support, Supervision, Feedback and Lecturers Role in the use of the Classroom Response Systems PINGO - Beutner, Marc; Kundisch, Dennis; Magenheim, J.; Zoyke, A. (Proceedings of the World Conference on E-Learning)

Formation and interaction of resonance chains in the open three-disk system - Weich, Tobias; Barkhofen, Sonja; Kuhl, U; Poli, C; Schomerus, H (New Journal of Physics)
Keywords: General Physics and Astronomy

X-Ray Photoelectron Spectroscopy Investigations of the Surface Reaction Layer and its Effects on the Transformation Properties of Nanoscale Ti51Ni38Cu11Shape Memory Thin Films - König, Dennis; Naujoks, Dennis; de los Arcos de Pedro, Maria Teresa; Grosse-Kreul, Simon; Ludwig, Alfred (Advanced Engineering Materials)

Description of HiPIMS plasma regimes in terms of composition, spoke formation and deposition rate - de los Arcos de Pedro, Maria Teresa; Schröder, Raphael; Gonzalvo, Yolanda Aranda; Gathen, Volker Schulz-von der; Winter, Jörg (Plasma Sources Science and Technology)

Carbon nanotube growth on AlN support: Comparison between Ni and Fe chemical states and morphology - Eren, Baran; Marot, Laurent; Steiner, Roland; de los Arcos de Pedro, Maria Teresa; Düggelin, Marcel; Mathys, Daniel; Goldie, Kenneth N.; Olivieri, Vesna; Meyer, Ernst (Chemical Physics Letters)

Simultaneous characterization of static and induced magnetic fields in high power impulse magnetron sputtering discharges - Machura, P D; Hecimovic, A; Gallian, S; Winter, J; de los Arcos de Pedro, Maria Teresa (Plasma Sources Science and Technology)

Adsorption and reactivity of nitrogen atoms on silica surface under plasma exposure - Marinov, D; Guaitella, O; de los Arcos de Pedro, Maria Teresa; von Keudell, A; Rousseau, A (Journal of Physics D: Applied Physics)

Nanostructured Er2O3 Thin Films Grown by Metalorganic Chemical Vapour Deposition - Xu, Ke; Dang, Van-Son; Ney, Andreas; de los Arcos de Pedro, Maria Teresa; Devi, Anjana (Journal of Nanoscience and Nanotechnology)

Approximation of the dual problem for error estimation in inelastic problems - Widany, Kai-Uwe; Mahnken, Rolf (PAMM)

Macroscopic and mesoscopic modeling based on the concept of generalized stresses for cutting simulation - Cheng, Chun; Mahnken, Rolf; Uhlmann, Eckart; Ivanov, Ivan Mitkov (PAMM)

A macroscopic consitutive model on induced anisotropy for polymers with weighting functions - Dammann, Christian; Mahnken, Rolf (PAMM)

Experimental Investigation of PC-Films Using Optical Measurements - Dammann, C.; Caylak, Ismail; Mahnken, Rolf (International Polymer Processing)
Abstract The alignment of polymer chains is a well known microstructural evolution effect due to straining of polymers. This has a drastic influence on the macroscopic properties of the initially isotropic material. In this work, cold forming is performed at room temperature on a tensile testing machine. Polycarbonate films are examined in two loading phases. In the first phase, the specimen is loaded to induce anisotropy, and in the second, it is re-loaded, while the material direction is varied. The investigations are supported by an optical measurement system to gain knowledge about the inhomogeneous material behavior in the initial loading phase and about the anisotropic homogeneous behavior during the re-loading phase. Two dimensional strain contours are obtained from the test data. Additionally, we propose a method for approximation of the macroscopic true stress and compare the results with a common approach based on volume consistency. In the future, the test data will set a basis for parameter identification of constitutive equations taking into account a combination of inhomogenous and homogenous material behavior, exhibiting strain induced anisotropy.

Self-Reinforced Thermoplastic Composites - Composite Materials (Part 1) - Heim, Hans-Peter; Ries, Angela; Sch {\ "o} ppner, Volker; Wibbeke,, Andrea; Turek, Stefan; Damanik, Hogenrich; Mahnken, Rolf; Dammann, Christian; W {\ "u} nsch, Olaf; Al-Baldawi, Ammar; Rohde, Bj ö rn; Br {\ "u} ckner-Foit, Angelika; et al. (Kunststoffe international})
With self-reinforced thermoplastics, it is possible to produce composite systems that, unlike traditional fiber composite materials, do not contain any foreign fibers for reinforcement. Instead, thermoplastic fibers or tapes, for example made of PP or PE, are used in an identical matrix. This opens up a high potential for lightweight construction and, at the same time, very good recyclability.

Multi-scale modeling of bainitic phase transformation in multi-variant polycrystalline low alloy steels - Mahnken, Rolf; Schneidt, A.; Antretter, T.; Ehlenbröker, U.; Wolff, M. (International Journal of Solids and Structures)

On the simulation of strain induced anisotropy for polymers - Dammann, C.; Mahnken, Rolf

Determinants of corporate participation in the IFRS 4 (insurance contracts) replacement process - Kosi, Urska; Reither, Antonia (Accounting in Europe)
This study examines the determinants of financial firms' lobbying behaviour in the replacement process of International Financial Reporting Standard 4 (IFRS 4) Insurance Contracts. Based on comment letters in response to International Accounting Standards Board's (IASB) Exposure Draft 2010/8, we investigate firms' lobbying decisions and their long-term lobbying intensity. Using an international sample of publicly listed financial firms, we show that insurance companies and financially constrained IFRS firms are more likely to lobby the IASB. We also examine the long-term lobbying activity in the IFRS 4 replacement process during the years 2007–2010. We find that insurance companies and firms with dispersed ownership lobby more. Our results are stronger for IFRS firms compared to US generally accepted accounting principles users. Overall, we document intense lobbying by financial firms and present results that are largely consistent with economic consequences of anticipated accounting changes being the main driver of firms' lobbying behaviour. These results are in line with prior findings for non-financial firms.
Keywords: standard setting; IASB; corporate lobbying; financial firms; IFRS 4

Polymer-stabilized blue phases: promising mesophases for a new generation of liquid crystal displays - Nordendorf, G.; Hoischen, A.; Schmidtke, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Columnar molecular aggregation in the aqueous solutions of disodium cromoglycate - Agra-Kooijman, Dena M.; Singh, Gautam; Lorenz, Alexander; Collings, Peter J.; Kitzerow, Heinz-Siegfried; Kumar, Satyendra (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Synthesis of Liquid Crystal Silane-Functionalized Gold Nanoparticles and Their Effects on the Optical and Electro-Optic Properties of a Structurally Related Nematic Liquid Crystal - Mirzaei, Javad; Urbanski, Martin; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Nanoparticle Doping in Nematic Liquid Crystals: Distinction between Surface and Bulk Effects by Numerical Simulations - Urbanski, Martin; Mirzaei, Javad; Hegmann, Torsten; Kitzerow, Heinz-Siegfried (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Planar anchoring strength and pitch measurements in achiral and chiral chromonic liquid crystals using 90-degree twist cells - McGinn, Christine K.; Laderman, Laura I.; Zimmermann, Natalie; Kitzerow, Heinz-Siegfried; Collings, Peter J. (Physical Review E)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Strategy and Management; Mechanical Engineering

Alfred Saupe Prize 2013 Laudatio for Prof. Dr Gerd Heppke* - Kitzerow, Heinz-Siegfried (Liquid Crystals Today)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

PU-CMA-QAM BASED MIMO EQUALIZATION IN DSP-ENABLED PDM-16-QAM RECEIVERS - Panhwar, M. F.; Sandel, D.; Woerdehoff, C.; Puntsri, K.; Hussin, S.; Noé, Reinhold (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

Fiber nonlinearity Mitigation in CO-OFDM Systems using Dual Compensators - Hussin, S.; Noé, Reinhold (2014 IEEE PHOTONICS CONFERENCE (IPC))

REALTIME DIGITAL SIGNAL PROCESSING IN COHERENT OPTICAL PDM-QPSK AND PDM-16-QAM TRANSMISSION - Noé, Reinhold; Panhwar, M. F.; Woerdehoff, C.; Sandel, D. (2014 PROCEEDINGS OF THE 22ND EUROPEAN SIGNAL PROCESSING CONFERENCE (EUSIPCO))

SIMPLE POLARIZATION-DEPENDENT LOSS MEASUREMENT BASED ON POLARIZATION SCRAMBLING - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

Versatile endless optical polarization controller/tracker/demultiplexer - Koch, Benjamin; Noé, Reinhold; Sandel, David; Mirvoda, Vitali (OPTICS EXPRESS)

IMPROVEMENT OF RF-PILOT PHASE NOISE COMPENSATION FOR CO-OFDM TRANSMISSION SYSTEMS VIA COMMON PHASE ERROR EQUALIZER - Hussin, S.; Noé, Reinhold; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

40 dB CROSSTALK SUPPRESSION IN HIGH-PRECISION ENDLESS POLARIZATION CONTROL - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

APD-BASED INTERFERENCE DETECTORS YIELD 7-dB DYNAMIC RANGE OF 70-krad/s PDM-DPSK ENDLESS POLARIZATION DEMULTIPLEXER - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

1-THz Bandwidth of 70-krad/s Endless Optical Polarization Control - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali; Sandel, David (2014 OPTICAL FIBER COMMUNICATIONS CONFERENCE AND EXHIBITION (OFC))

APD-BASED INTERFERENCE DETECTORS YIELD 7-dB DYNAMIC RANGE OF 70-krad/s PDM-DPSK ENDLESS POLARIZATION DEMULTIPLEXER - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

40 dB CROSSTALK SUPPRESSION IN HIGH-PRECISION ENDLESS POLARIZATION CONTROL - Koch, B.; Noé, Reinhold; Mirvoda, V.; Sandel, D.; Panhwar, M. F. (2014 OPTOELECTRONICS AND COMMUNICATIONS CONFERENCE AND AUSTRALIAN CONFERENCE ON OPTICAL FIBRE TECHNOLOGY (OECC/ACOFT 2014))

1-THz bandwidth of 70-krad/s endless optical polarization control - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali; Sandel, David (OFC 2014)

Die Schweigsame Frau – Friedenstag – Daphne - Grotjahn, Rebecca (Richard Strauss Handbuch)
Die schweigsame Frau, Friedenstag und Daphne hängen in ihrer Entstehung eng miteinander zusammen — sowohl über die Arbeitsbeziehungen des Komponisten mit den Textdichtern Stefan Zweig und Joseph Gregor als auch über die politischen Bedingungen in den ersten Jahren des NS-Regimes. Der Text der Schweigsamen Frau stammt vollständig von Zweig. Friedenstag wurde von ihm zwar weitgehend konzipiert, aber von Gregor ausgearbeitet. Daphne erarbeitete Gregor zwar nach einer eigenen Idee als Schwesterwerk zu Friedenstag, doch war Zweig auch jetzt noch für Gregor wie für Strauss Gesprächspartner und Ratgeber.

‚Eine Art Klauenseuche unter den Pensionatstöchtern und den Mädchen überhaupt‘: Klavier, Gender und Massenkultur - Grotjahn, Rebecca (Geburt der Massenkultur. Beiträge der Tagung des WGL-Forschungsprojekts Wege in die Moderne. Weltausstellungen, Medien und Musik im 19. Jahrhundert im Germanischen Nationalmuseum)

Familien- und Elternbildung im Kontext sozialen Wandels und sozialer Ungleichheiten - Landhäußer, Sandra (Sozialer Wandel. Herausforderungen für Kulturelle Bildung und Soziale Arbeit)
Tiefgreifende soziale Wandlungsprozesse und veränderte Selbstbeschreibungen moderner Gesellschaften - verbunden mit Forderungen nach und Versprechungen von mehr Bildung und lebenslangem Lernen - beschreiben ein umfangreiches Bündel an Herausforderungen für Kulturelle Bildung und für Soziale Arbeit. Der Band greift aktuelle gesellschaftliche Entwicklungen und Fragen in diesem Zusammenhang auf, z.B. zur Bedeutung von Bildung, Kultur und Werte in der Wissens- und Informationsgesellschaft, im Kontext von Globalisierung, mit Blick auf ein sich veränderndes Generationenverhältnis oder in Bezug auf Interkulturalität und Integration. Im Vordergrund steht die Neuthematisierung des Kulturellen sowie des Sozialen im Hinblick auf Chancen, Anforderungen und Illusionen, die sich Kindern, Jugendlichen und Erwachsenen in ihrer Lebensbewältigung und Lebensgestaltung stellen sowie in Bezug auf die Weiterentwicklung pädagogischer Angebote und Institutionen vor diesem Hintergrund. (Verlag).
Keywords: Jugend; Menschenrechte; Sozialer Wandel; Globalisierung; Elternbildung; Familienbildung; Kulturelle Bildung; Kulturpädagogik; Sozialpädagogik; Sozialarbeit; Aufsatzsammlung

2-Hydroxyethylammonium iodide - Kohrt, Christina; Spannenberg, Anke; Werner, Thomas (Acta Crystallographica Section E Structure Reports Online)
In the crystal structure of the title salt, C 2 H 8 NO + ·I − , N—H...O, N—H...I and O—H...I hydrogen bonds lead to the formation of layers staggered along the c axis.
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

A Catalytic System for the Activation of Diorganozinc Reagents - Werner, Thomas; Bauer, Matthias; Riahi, Abdol Majid; Schramm, Heiko (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

First Microwave-Assisted Catalytic Wittig Reaction - Werner, Thomas; Hoffmann, Marcel; Deshmukh, Sunetra (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

First Enantioselective Catalytic Wittig Reaction - Werner, Thomas; Hoffmann, Marcel; Deshmukh, Sunetra (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Synthesis of cyclic carbonates from epoxides and CO2 catalyzed by potassium iodide and amino alcohols - Werner, Thomas; Tenhumberg, Nils (Journal of CO2 Utilization)
Keywords: Process Chemistry and Technology; Waste Management and Disposal; Chemical Engineering (miscellaneous)

Phosphorus-based Bifunctional Organocatalysts for the Addition of Carbon Dioxide and Epoxides - Werner, Thomas; Büttner, Hendrik (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Hydroxyl-Functionalized Imidazoles: Highly Active Additives for the Potassium Iodide-Catalyzed Synthesis of 1,3-Dioxolan-2-one Derivatives from Epoxides and Carbon Dioxide - Werner, Thomas; Tenhumberg, Nils; Büttner, Hendrik (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Bifunctional One-Component Catalysts for the Addition of Carbon Dioxide to Epoxides - Büttner, Hendrik; Lau, Kornelia; Spannenberg, Anke; Werner, Thomas (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Parameter identification for rubber materials with artificial higher dimensional data - Mahnken, Rolf; Nörenberg, Nicole (PAMM)

Bainitic variant evolution in a low-alloyed steel including numerical aspects - Ehlenbröker, Ulrich; Mahnken, Rolf (PAMM)

Self-Reinforced Thermoplastic Composites - Composite Materials (Part 2) - Heim, Hans-Peter; Ries, Angela; Sch {\ "o} ppner, Volker; Wibbeke, Andrea; Turek, Stefan; Damanik, Hogenrich; Mahnken, Rolf; Dammann, Christian; W {\ "u} nsch, Olaf; Al-Baldawi, Ammar; Rohde, Bj ö rn; Br {\ "u} ckner-Foit, Angelika; et al. (Kunststoffe international)
Based on research results from the Collaborative Research Center Transregio 30, it is shown how composites made of self-reinforced, partially crystalline or highly stretched amorphous foils and fabrics for lightweight construction applications can be produced and which properties can be achieved. A locally differential, thermo-mechanical process control can be varied very efficiently, and thus graded properties can be set in the sense of functionalization.

Stabilized mixed triangular elements with area bubble functions at small and large deformations - Caylak, Ismail; Mahnken, Rolf (Computers & Structures)

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Koren, Jernej; Kosi, Urska; Valentincic, Aljosa (SSRN Electronic Journal)
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.

Measurement of group velocity dispersion in a solid-core photonic crystal fiber filled with a nematic liquid crystal - Wahle, Markus; Kitzerow, Heinz-Siegfried (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Liquid crystal assisted optical fibres - Wahle, M.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics